Analysis Of Social Development Of Early Children: Challenges And Solutions In The Digital Era - Hadisa Putri (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
The aim of the research is to describe and analyze the social development of early childhood in the digital age, uncover challenges and solutions faced by parents, teachers and society. This research method uses qualitative methods with the type of literature review research. Data sources use two kinds of data, namely primary data and secondary data. Primary data is obtained directly from collecting data from research journals, books, websites that are relevant to the study of early childhood social development in the digitalization era and secondary data sources (basic government legal regulations, books, etc.). The data analysis technique uses content analysis. The results of this study indicate that as many as 47% of parents spend all day in front of gadget screens, and most of their children already have an emotional bond with gadget devices. Solutions in more intensive surveillance research for parents in using smartphones at home, making certain programs to use gadgets. The recommendation from this study is that a special learning model is needed at home in using gadgets with certain programs in fostering social development.